Money and privacy: Android market evidence - Michael Kummer; Patrick Schulte (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
We study the role of privacy in the market for mobile applications. For such programs used with smartphones and tablet PCs a very important market has emerged. Yet, neither the role of privacy on that market is well understood, nor do we have empirical evidence regarding its role therein. We exploit data on 300,000 mobile applications and almost 600 "applications-pairs" to analyze both sides of this market: First, we analyze the price that application suppliers charge for more privacy. Second, we study how users' installations are related to the "personal data greediness" of mobile applications. We provide the first empirical evidence on the main assumptions of recent early models on suppliers' and consumers' strategies in this market. Our results show that (1) consumers take it into account when applications request rights to collect private information and (2) suppliers ask for more rights if they offer an app for free than if they offer it for a fee.
urn:nbn:de:bsz:180-madoc-375394
Keywords: D4; D83; L15; 330; Information Acquisition; Mobile Applications; Smartphones; Online Privacy; Permissions; Price; Privacy Regulation